Evidence-Based Dentistry Caries Risk Assessment and Disease Management - Hanaa Raheem Fahad (Journal of Global Pharma Technology, 2019)
Dental caries is a multifactorial, dynamic disease process that results from a dysbiosis in the biofilm, driven by exposure to fermentable carbohydrates, which over time leads to demineralization of dental hard tissues. In spite of the significant reduction in caries prevalence in many parts of the world, dental caries remains a major public health problem affecting people of all ages. Furthermore, the disease is not equally distributed, with multiple population groups at increased risk. If allowed to progress, over time the disease will result in the development of detectable changes in the tooth structure, or caries lesions, which initially are noncavitated (i.e., macroscopically intact, sometimes referred to as “white spot” or “incipient” lesions), but that eventually might progress to cavitation. Modern caries management stresses a conservative and preventive evidencebased philosophy, with patient-centered risk-based disease management, early detection of caries lesions, and efforts to remineralize and/or arrest noncavitated lesions that aim to preserve tooth structure and maintain health. In support of this philosophy, numerous systems and guidelines have been developed. Furthermore, this caries management philosophy is the basis for current cardiology education frameworks worldwide.Keywords:  Dentistry, Fluorides, Risk Assessment Disease, Risk Assessment Management.